Genetic Variation of Baram River Frog, Pulchrana baramica (Boettger, 1900), In Java, Sumatra, and Kalimantan based on 16S Mitochondrial Gene - Fauzi, Luthfi; Arisuryanti, Tuty; Aji, Katon Waskito; Riyanto, Awal; Smith, Eric N.; Hamidy, Amir (Universitas Gadjah Mada, 2024)
Baram River Frog (Pulchrana baramica) is a ranid species distributed in the Malay Peninsula, Borneo, Sumatra and represents the sole species from the genus Pulchrana on Java Island. Cryptic species are commonly encountered within the amphibian group which can cause confusion in the identification process. Due to the broad distribution range of P. baramica and the frequent occurrence of cryptic species within the amphibian group, it is important to evaluate the taxonomic status of P. baramica. Therefore, we investigated the taxonomic position of P. baramica from three populations (Kalimantan, Sumatra, and Java) and identified the interpopulation genetic variation based on molecular data of the 16S mitochondrial gene. We reconstructed phylogenetic relationships using Neighbour Joining, Maximum Likelihood, and Bayesian Inference. The research results revealed that Pulchrana baramica is a monophyletic group and nested within a group together with P. glandulosa and P. laterimaculata. The monophyletic group of P. baramica consisted of four distinct lineages that molecularly showed interspecific genetic variation. Clade 1 represents the population of Sumatra and Borneo (Kalimantan), clade 2 comprises the population from Borneo (Sarawak), clade 3 consists of population from Java, and clade 4 represents the population from Sumatra. Further research is required with the addition of morphological and acoustic data as supportive evidence to obtain more extensive comprehension of species identification.